If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -2m = -9 + -1m Solving -2 + -2m = -9 + -1m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add 'm' to each side of the equation. -2 + -2m + m = -9 + -1m + m Combine like terms: -2m + m = -1m -2 + -1m = -9 + -1m + m Combine like terms: -1m + m = 0 -2 + -1m = -9 + 0 -2 + -1m = -9 Add '2' to each side of the equation. -2 + 2 + -1m = -9 + 2 Combine like terms: -2 + 2 = 0 0 + -1m = -9 + 2 -1m = -9 + 2 Combine like terms: -9 + 2 = -7 -1m = -7 Divide each side by '-1'. m = 7 Simplifying m = 7
| 10(1a+3b)=-20 | | -6+7q=5q | | x+3=2x+1-x+2 | | 8. 4m+5n=25 | | 3(2x+4)=-2(4x-13) | | 4x^3-3x=13 | | -8y-9=-10y+9 | | -3/2=-2/5y-5/3 | | 1-2x+3=2x+8 | | -3/2=2/5y-5/3 | | ax-b=c(x-a) | | 6+14u=8 | | 13+3(3x+8)=x+3 | | -(x+3)+2=2x | | -8y-9=-10+9 | | 2/3u-8/9=-7/5 | | 6x=ln(10/9) | | 4x+-2y=18 | | 4k(-3mk)= | | 2/5×25 | | 5+7x(3+2)-16= | | 3x+4+x=4-x | | 36b+-10=-6 | | 45=5x-9+x | | -(1/7×3/2)= | | Y/10=9/4 | | 4c-16=8 | | -12u+7=-1 | | 3x^2-7x+3=2x^2-4x+3 | | j-3=7+6j | | 16/1 | | y^2-2xy+3=0 |